2009
DOI: 10.1104/pp.109.139204
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cell Wall Loosening by Hydroxyl Radicals during Cress Seed Germination and Elongation Growth    

Abstract: Loosening of cell walls is an important developmental process in key stages of the plant life cycle, including seed germination, elongation growth, and fruit ripening. Here, we report direct in vivo evidence for hydroxyl radical ( × OH)-mediated cell wall loosening during plant seed germination and seedling growth. We used electron paramagnetic resonance spectroscopy to show that × OH is generated in the cell wall during radicle elongation and weakening of the endosperm of cress (Lepidium sativum; Brassicaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
314
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(333 citation statements)
references
References 51 publications
12
314
0
7
Order By: Relevance
“…The lettuce seed endosperm when sown in isocyanuric acid is capable of resisting the expansion force of the embryo resulting in embryo expansion without endosperm rupture ("buckling") and protrusion at the cotyledon end or along the side ("atypical germination") [23]. Atypical germination was also reported with cress seeds [24].…”
Section: Introductionmentioning
confidence: 94%
“…The lettuce seed endosperm when sown in isocyanuric acid is capable of resisting the expansion force of the embryo resulting in embryo expansion without endosperm rupture ("buckling") and protrusion at the cotyledon end or along the side ("atypical germination") [23]. Atypical germination was also reported with cress seeds [24].…”
Section: Introductionmentioning
confidence: 94%
“…Studies on leaf expansion in maize under saline conditions revealed a decreased O 2 2 -derived _ OH production in the apoplast and a consequent reduction in leaf growth (Rodríguez et al, 2004). Interestingly, it was found that _ OH promotes cell elongation by loosening the cell wall through oxidative cleavage of polymers like xyloglucan and pectin (Fry, 1998;Müller et al, 2009). In the presence of transition metals, the Haber-Weiss reaction can convert H 2 O 2 and O 2 2 anions to _ OH, a reaction that can be performed both nonenzymatically as well as enzymatically (Chen and Schopfer, 1999).…”
Section: Ros In the Apoplast: The Oxidant's Playgroundmentioning
confidence: 99%
“…However, many basic processes involved in cell wall growth and dynamics require a highly oxidizing environment. Unlike the cell interior, the wall requires the generation of strong oxidants such as the hydroxyl radical (Müller et al, 2009). Consequently, the apoplast has evolved a relatively low capacity for antioxidant accumulation, together with enzymes that actively remove these compounds (Pignocchi and Foyer, 2003;Ohkama-Ohtsu et al, 2007;Parsons and Fry, 2012).…”
mentioning
confidence: 99%